Systemic Innovation Entrepreneurial Strategies and Market Dynamics. - Uzunidis, Dimitri (John Wiley & Sons, Incorporated, 2020)
INNOVATION IN ENGINEERING AND TECHNOLOGY SET Coordinated by Dimitri Uzunidis Systemic innovation is based on business networks and new business models in a global economy integrated by flows of knowledge, capital, and goods. The authors of this book consider the theory that innovations act as systems based on multi-actor interactions. Innovation is contextualized to demonstrate in what capacity a company or an entrepreneur can innovate. The book details the management of scientific, technical and cognitive resources, the relationships between R&D partners, the creativity and the rules that allow a market and a company to innovate. This contextualization, associated with entrepreneurial strategy, leads to systemic innovation. This book analyzes some key sectors of the economy that are knowledge-intensive and rapidly changing: transport and communications, defense, information technology, artificial intelligence, and the environment.